A Village House Energy-Supply System: Fundamentals of Energy Conversion - Kurtulan, Salman; Sevgi, Levent (Institute of Electrical and Electronics Engineers (IEEE), 2009)
A village house energy system is discussed. Power requirements and daily energy consumption of a medium-size, one-floor house, with typical household appliances, are given. Block diagrams of a solar-energy system, a wind-power system, a hydroelectric-power system, and a fuel-oil power system are presented.
Keywords: Wind Power System; Green Energy; Solar Energy; Fuel Oil Power; Solar Power System; Hydroelectric Power System; Energy Conversion